The Impact of an Undergraduate Community‐Based Medical Education Program in a Japanese Urban City - Hiramine, Satoshi; Nagata, Masaharu; Kainuma, Mosaburo (Cureus, 2024)
With an aging global population posing healthcare challenges, especially in community healthcare, training professionals for community healthcare remains a global educational challenge, including in Japan. While previous research shows increased student interest in community healthcare through practical experiences, the focus has primarily been on rural areas, leaving a gap in understanding urban-based community medical education. This study aimed to evaluate the impact of urban community-based medical education on students' understanding and attitudes toward community healthcare. This study was conducted at Kyushu University in Fukuoka City, the sixth-largest city in Japan. For fifth-grade medical students, a community-based medical education program is mandatory, with a one-week schedule that includes orientation, one day in a clinic, and three days in a community hospital. The program aimed to expose students to various healthcare settings, emphasizing outpatient care, inpatient management, home health care, home nursing, and rehabilitation. A self-administered questionnaire referencing the Model Core Curriculum for medical education was administered immediately before and after the program, and the differences in students' perceptions were assessed using the Student's t-test. Findings from 188 students completing both pre- and post-program questionnaires revealed significant improvements in perceptions of students' knowledge and skills related to community healthcare. After the training, there was a noteworthy positive shift in attitudes toward community healthcare and increased interest in primary care physicians as a career choice. Although students maintained a preference for urban areas, there was a notable inclination towards rural settings. The study highlights the program's success in enhancing students' understanding and positive attitudes toward community healthcare within an urban context. It challenges prior notions regarding work-life balance and urban-rural preferences in career choices. Urban community-based medical education significantly improved students' perceptions and attitudes toward community healthcare. It offers valuable insights for curriculum planners, emphasizing the need for continued research into sustained effects and broader applicability.